PERENCANAAN PERKERASAN PARALEL TAXIWAY SELATAN DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI - BALI - supriadi supriadi; abrian amirullah; nurani hartatik (Jurnal Penelitian)
I Gusti Ngurah Rai International Airport, as it is known, is taken from the name of national hero I Gusti Ngurah Rai who is a very influential figure for the people of Bali Island. I Gusti Ngurah Rai International Airport currently has 11 taxiways which are divided into 9 taxiways on the North runway / North (2 parallel taxiways, 2 rapid exit taxiways, and 5 exit taxiways) and 2 taxiways on the South runway. This writing uses primary and secondary data which will be analyzed by descriptive analysis method. Descriptive analysis method is research that is intended to collect information about the status - the status of a symptom that exists, namely the state of symptoms according to what they were when the study was conducted. The author also uses the pavement design application in the form of FAARFIELD and COMFAA to support the research method used. Therefore, to be able to receive loads from aircraft passing through taxiways, it is necessary to calculate the planing of the pavement on the taxiways that will be built so that they are able to withstand the loads that will be received for flight safety and fulfill the age of the plan itself. The new taxiway parallel to the south of the runway needs to be built to support the operational activities of the annual IMF (International Monetary Fund) activities and taxiway overlaying in all North taxiways. In addition, it is expected to reduce the number of aircraft carrying out cross runways from the southern apron to the northern apron or to the northern taxiway parallel.